Effect of hermetic storage on the quality and shelf life of ‘Obatampa’ maize (Zea mays L.) variety - Diarra, Mamoutou (University of Cape Coast, 2016)
Control of the storage pest Larger Grain Borer (LGB) (Prostephanus truncates) and aflatoxin contamination by the mould Aspergillus spp. are the major challenges to maize storage in Africa. In this study, the effect of hermetic storage on LGB and Aspergillus spp. during maize storage was evaluated. A 2 x 3 factorial experiment of two storage atmospheres (hermetic and non-hermetic) and infestation levels (LGB, Aspergillus spp. and uninfected control) were evaluated during the storage of ‘Obatampa’ maize. LGB and Aspergillus spp. were each introduced into 1.5 kg of the maize grains in hermetic and non-hermetic bags and stored alongside uninfected grains of same weight. Oxygen depletion in the hermetic bags was significant (p = 0.012) while temperature in both hermetic and non-hermetic bags remained fairly constant at 26.99 ºC and 27.4 ºC, respectively. Relative humidity, moisture content, grain damage and weight loss percentages were significantly different in the various bags (p < 0.001). There was 100 % LGB mortality in the hermetic storage after 52 days. Aspergillus flavus contamination in the non-hermetic bags was highly significant compared to the hermetic bags (p = 0.002). The aflatoxin group B2 was found in both storage systems. While the aflatoxin group G1 was not detected, the G2 group was only detected at the concentration 0.1 ppb in the hermetic storage. The double layer hermetic SuperGrainbag better preserved the quality and shelf life of the maize grains and maintained seed viability (p < 0.001) much longer than the non-hermetic polypropylene bag.
xiv, 157p:,ill.
Keywords: 'Obatampa’ maize; Hermetic storage; Variety